Investigating the Cognitive Load Drivers of Software Evolution Activities - Belém, Patrick; Mello, Rafael De; Vivacqua, Adriana S.; Souza, Adriano Neves De (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Cognitive load theory proposes a framework to characterize the mental effort employed by individuals in their tasks. To properly measure the cognitive load of a certain activity, it is important to know its drivers, which may vary according to the nature of this activity. We report, in this paper, initial results of an investigation of the cognitive load drivers of software evolution activities. After analyzing the content of semi-structured interviews conducted with members of a software maintenance team, we found a set of problems and difficulties they experience when evolving software systems. Based on this set, we mapped a preliminary version of cognitive load drivers of software evolution activities.